Os desafios do novo ensino médio na prática dos professores de química e biologia em uma escola estadual de Itacoatiara - AM - Camelo, Adriana do Santo (Brasil, 2024)
The present research aimed to identify the challenges of the new high school model, which began to adopt the National Commom Curricular Base (BNCC) from 2022, in the perception of Chemistry and Biology teachers who work in a state school in the city of Itacoatiara – AM, in the state of Amazonas. This is a qualitative, field research, whose data collection instrument was a semi- structured interview, with five professors who graduated from the Bachelor of Science course: Chemistry and Biology at ICET.The teachers interviwed reported the challenges of implementing a proposal wilhout na indepth discussion,anchored in a consistent contiming education process; Without investment inphysical structure and pedagogical resources; in addition to a reduction inworkload that makes it impossible for all necessary content to be taught.